Influence of the concentration of H2–D2 mixtures on their triple-point dewetting behavior: Physics in Quantum Crystals - Tibus, Stefan; Sohaili, Masoud; Klier, Jürgen; Leiderer, Paul (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Triple-point dewetting of pure gases like hydrogen and deuterium on solid substrates is a well-known phenomenon. This property persists even for the mixed system of H2 and D2. There exists an effective triple-point temperature T3(mix) , between the T3 of pure H2 and the one of pure D2, which depends on the species concentrations. We present new investigations for a wide range of H2–D2 concentrations measured under different thermodynamic conditions. This allows us to map out T3(mix) as function of concentration, which can be different in the melting or solidifying direction. Furthermore, it turns out that the time the system needs to reach an equilibrium state can be very long and depends on concentration. This is not observed for the pure H2 and D2 system. Sometimes the relaxation times are so extremely long that significant hysteresis occurs during ramping the temperature, even if this is done very slowly on a scale of hours. This behavior can be understood on the basis of mixing and demixing processes. Possible differences in the species concentrations in the gas, liquid, and especially solid phase of the system are discussed. A preliminary phase diagram of the H2–D2 system is established.